The Influence Of Application Of The Cooperative Integrated Reading And Composition (CIRC) Learning Model On Reading Comprehension Ability In Indonesian Language Subjects Of Grade V Students Elementary Schools In Makassar City - Putri, Nabila Amaliah; Achmad, Widya Karmila Sari; Tati, Andi Dewi Riang (International Journal of Elementary School Teacher, 2024)
This research is motivated by the problem of the lack of students' reading comprehension skills in the Indonesian language subject of grade V elementary school. The purpose of this study was to determine the description of the application of the Cooperative Integrated Reading and Composition (CIRC) learning model in learning Indonesian, to determine the description of students' reading comprehension skills in learning Indonesian and to determine the effect of the application of the CIRC learning model on students' reading comprehension skills in the Indonesian language subject of grade V elementary school students. This study uses a quantitative approach. The method used in this study is the Quasi Experimental Design approach. The population in this study were all students of grade V UPT SPF SD Negeri Kassi, Manggala District, Makassar City and the research sample was class V A as an experimental class totaling 20 students and class V B as a control class totaling 20 students. The sampling technique was the saturated sample technique. The instruments used were non-tests (observation sheets) and written tests (pretest and posttest) totaling 10 questions (fill-ins). The results of the statistical analysis showed that there was a significant difference between the experimental group and the control group in terms of reading comprehension ability, which means that the application of the CIRC model has a positive effect. This model has also been proven to be well implemented, as seen from the increase in the observation result category from "good" to "very good". The pretest scores of both groups were in the less category, but the posttest scores of the experimental group reached the good category, while the control group remained in the sufficient category. So it can be concluded that there is an effect of the application of the CIRC learning model on the reading comprehension ability of class V students of UPT SPF SD Negeri Kassi, Manggala District, Makassar City.